Application of the ex-Gaussian function to the effect of the word blindness suggestion on Stroop task performance suggests no word blindness - Parris, Benjamin A.; Dienes, Zoltan; Hodgson, Timothy L. (Frontiers in Psychology, 2013)
The aim of the present paper was to apply the ex-Gaussian function to data reported by Parris et al. (2012) given its utility in studies involving the Stroop task. Parris et al. showed an effect of the word blindness suggestion when Response-Stimulus Interval (RSI) was 500ms but not when it was 3500ms. Analysis revealed that: 1) The effect of the suggestion on interference is observed in µ, supporting converging evidence indicating the suggestion operates over response competition mechanisms; and, 2) Contrary to Parris et al., an effect of the suggestion was observed in µ when RSI was 3500ms. The reanalysis of the data from Parris et al. (2012) supports the utility of ex-Gaussian analysis in revealing effects that might otherwise be thought of as absent. We suggest that word reading itself is not suppressed by the suggestion but instead that response conflict is dealt with more effectively.